Live-Attenuated Respiratory Syncytial Virus Vaccine With Deletion of RNA Synthesis Regulatory Protein M2-2 and Cold Passage Mutations Is Overattenuated. (6th May 2019) - Cunningham, Coleen K; Karron, Ruth; Muresan, Petronella; McFarland, Elizabeth J; Perlowski, Charlotte; Libous, Jennifer; Thumar, Bhagvanji; Gnanashanmugam, Devasena; Moye, Jack; Schappell, Elizabeth; Barr, Emily; Rexroad, Vivian; et al.
Abstract: Background: The live respiratory syncytial virus (RSV) candidate vaccine LIDcpΔM2-2 is attenuated through deletion of M2-2 and 5 cold-passage mutations. Methods: RSV-seronegative children aged 6–24 months received a single intranasal dose of 10 5 plaque-forming units (PFU) of LIDcpΔM2-2 or placebo. RSV serum antibodies, vaccine infectivity, and reactogenicity were assessed. Results: Four of 11 (36%) vaccinees shed vaccine virus with median peak titers of 1.6 log10 PFU/mL by quantitative culture and 4.5 log10 copies/mL by polymerase chain reaction; 45% had ≥4-fold rise in serum-neutralizing antibodies. Respiratory symptoms or fever were common in vaccinees (64%) and placebo recipients (6/6, 100%). Conclusions: RSV LIDcpΔM2-2 is overattenuated. Clinical Trial Numbers.  NCT02890381, NCT02948127.